Zeev Sternhell (1935-2020): fra «destra rivoluzionaria» e ideologia fascista - Germinario, Francesco (——— Materialismo Storico ——— Rivista di filosofia, storia e scienze umane, 2022)
Zeev Sternhell's work is a real historiographic model, focused on the enhancement of French political and philosophical cultures between the last twenty years of the nineteenth century and the eve of the First World War. The debate on Sternhell's positions has been an important aspect of the historiographic debate on fascism for at least forty years. However, there is a point that has never been treated in this debate: the role played by violence in the fascist ideological universe. It is a decisive point, because it characterizes the fascist attitude towards reality. Hence the historiographic need to interpret fascism as the activist version of the “revolutionary right”. Revolutionary Right; Fascist Ideology; Political Violence.